Evaluación de la capacidad de biofijación de CO2 de un cultivo de microalgas en un proceso de combustión fija (2020)
This project considers the ability of microalgae to capture the CO2 derived from a real combustion process. For this, a system consisting of a rocket gasifier was built, in which rice husk was specified as fuel in order to take advantage of this residue and generate the combustion gas necessary to supply three photobioreactors with a known volume of This gas, in this way determine the volume that generates a greater growth of the crop and biofixation of CO2 by the microalga. For this, three tests were carried out, in which the growth of the Chlorella vulgaris microalgae was evaluated under different volumes of combustion gas injection, which were 20, 30 and 50 ml of this gas, showing a better growth with the first injection, which contains 0.000757 moles of CO2, which when captured, contain a biofixation of 0.254 g / L * d. This figure translates into the production of 0.335 g of biomass per liter of culture, a fact that demonstrates the capacity of biofixation of CO2 by these microorganisms even under the presence of the other gases generated in a fixed combustion process.